Chemistry for green environment - Srivastava, M.; Sanghi,Rashmi ([S.l.] : Alpha Science International, Ltd, 2005)
"Chemistry for Green Environment" provides an overview of the current status of Chemistry for implementation of clean, ecofriendly, less wasteful manufacturing process and introduces new emerging green face of multi-dimensional Chemistry highlighting the need, principle, evolution, strategies and bioethical concerns for sustainable development of environment. It addresses important topics such as Information Processing, Information Building, Bioinformatics, Green Computation, Ecofriendly Technologies for Clean World, Green Processes: Emerging Trends, Combinatorial effects of synthetic and natural pesticides, Plant Based Products-Green Perspectives, Standardization approach for herbal products and Recent trends in drug development through Ethno botany.
Keywords: chemistry,environment,green envronment